Fridays for Future: Analysis of the Fundamental Communicative-Action Patterns of a Hashtagged Global Movement Lead by Stakeholders - Samuel Oliveira, Evandro; Ruiz-Mora, Isabel María; Rodríguez-Amat, Joan Ramón; Zeler, Ileana (My University, 2022)
The purpose of this study is to analyse the socio-communicative aspects of Fridays For Future as a hashtagged movement on Twitter and its implications; paying particular attention to the discussion and mobilisation that have grown over and above the reach of any NGO previously. It also considers the ways those actions drip into the public debates and social change, the organisation constitution, as well as the strategic communication dimension of activists as central agents within activists groups. A sample of 5 non-consecutive weeks during the first half of 2021 with a similar number of Twitter activity containing the hashtags #fridaysforfuture, #climatestrike and #schoolstrike4climate was analysed using the academic research API v2 and Python scripts. Qualitative and quantitative methods were used to evaluate the data in three different approaches: descriptive analysis, network analysis and attribute analysis. Results show an ongoing intensive discourse and societal process about the issue produced by different social actors involved in the communicative process. There is an orderly (dis)organisation that allows us to visualise patterns of strategic behaviour. The conversation around hashtags and the participation in actions are evidence of the purpose of a fluid disruptive organisational form and its strategic communication.
Keywords: movimientos sociales; Calentamiento global; Medios sociales; social movement; strategic communication; Fridays for Future; communication patterns; Twitter; Hashtag; stakeholders